Executive Committee Minutes 2010-04-22 - Academic Senate:::::::::
Revision to the Biology Minor approved for Senate consent calendar. Move of Organizational Development from Psychology to Hutchins approved for Senate consent calendar. Diversity Recommendations Survey Report approved for Senate agenda.